New Dynamics for Europe: Reaping the Benefits of Socio-ecological Transition. Synthesis Report Part I. Executive Summary - Karl Aiginger; Margit Schratzenstaller (WWWforEurope, 2016)
The European project is a long-run success story. Up to the 1990s, Europe thrived and experienced rising prosperity, as well as a catching up process with technology frontiers, while simultaneously extending its welfare model. The integration process, starting with six member states, led to a single market of 28 countries. It culminated in the creation of a currency union for 330 million Europeans. The political integration of former communist countries and their economic catching-up with Western Europe were achieved at an unprecedented historical pace. European integration has never been a smooth process. Stress during the process was referred to under the lemma of "eurosclerosis" and entailed competitive devaluations. The Lisbon Strategy was never fully implemented. Disappointment was counter-balanced by "Europe 2020", which intended to address structural problems and give the member states a greater opportunity to adapt the strategy to their specific situations. The financial crisis quickly spread from the US to Europe, highlighting unresolved governance issues and neglected public sector reforms. These also prevented adequate responses to new problems and opportunities arising from globalisation, technology, demography, the environment and most recently the refugee crisis ...
Keywords: 330; Strukturwandel; Wirtschaftliche Anpassung; Sozialer Wandel; Nachhaltige Entwicklung; Europa